2019
DOI: 10.1111/ped.14006
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide survey of pediatric hypodiploid acute lymphoblastic leukemia in Japan

Abstract: Background Ploidy is a highly significant prognostic factor for pediatric acute lymphoblastic leukemia (ALL). Children with hypodiploid ALL have poor outcomes despite current intensive chemotherapy. Little has been investigated with regard to hypodiploid ALL in Japanese children. Methods We retrospectively collected clinical data on hypodiploid ALL cases from the registries of prospective multicenter trials conducted by the four independent clinical study groups in Japan between 1997 and 2012. Results A total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…In the pediatric population with hyperdiploid B-ALL, the median age at diagnosis is 4 years in both Asian and European populations [64,104,128]. Several studies in Asian countries have found higher proportions of women in groups with high hypodiploidy, in contrast to the European population, where there is a higher proportion of men [41,104,128]. Patients with chromosomes 40-44 seem to have more in common with the 45-chromosome group than those with less than 40 chromosomes [103,106].…”
Section: High Hypodiploidymentioning
confidence: 99%
See 2 more Smart Citations
“…In the pediatric population with hyperdiploid B-ALL, the median age at diagnosis is 4 years in both Asian and European populations [64,104,128]. Several studies in Asian countries have found higher proportions of women in groups with high hypodiploidy, in contrast to the European population, where there is a higher proportion of men [41,104,128]. Patients with chromosomes 40-44 seem to have more in common with the 45-chromosome group than those with less than 40 chromosomes [103,106].…”
Section: High Hypodiploidymentioning
confidence: 99%
“…National Cancer Institute (NCI) analysis indicates that only measurable residual disease (MRD) at the end of induction (EOI) is a significant predictor of EFS in near-haploid and low-hypodiploid B-ALL groups [113]. Several groups escalated treatment based on MRD-based stratification protocols are associated with a better outcome after adjusting for sex, age, and leukocyte count, with a 5-year EFS of 62% [39,128,129]. Hematopoietic stem cell transplantation (HSCT) is often performed in first complete remission (CR1) and is traditionally reserved for pediatric patients with a very poor prognosis (EFS 50%), including patients with hypodiploidy (<44 chromosomes) [123,130].…”
Section: Low Hypodiploidymentioning
confidence: 99%
See 1 more Smart Citation
“…Hypodiploidy -the loss of one or more whole chromosomes- is a rare cytogenetic finding (≤7%) in children and adults with B-ALL and is generally an adverse prognostic marker [ 12 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. Most cases (~80%) of hypodiploid B-ALL present with 45 chromosomes and are classified as near-diploid B-ALL, a clinically distinct entity characterized by rearrangements that form dicentric chromosomes but that does not have outcomes as poor as those associated with hypodiploid B-ALL [ 21 ].…”
Section: Definition Of Hypodiploid B-all Subgroupsmentioning
confidence: 99%
“…The low EFS rates observed in near-haploid and low-hypodiploid groups are related to a high relapse rate mostly from isolated BM relapses, and succumbing to the disease after first remission [ 24 , 25 ] ( Table 5 ). According to the review by Groeneveld-Krentz et al on patients with relapsed BCP-ALL [ 68 ], those with pediatric B-ALL with hypodiploidy <40 chromosomes show specific characteristics compared with other B-ALL groups, including: (i) association with older age at initial diagnosis, (ii) shorter time to first relapse, (iii) more frequent allocation to the high-risk treatment arm of the relapse trial, and (iv) inferior second remission rates [ 68 ].…”
Section: Outcome and Treatment Strategies For B-all With Hypodiploidies <40 Chromosomesmentioning
confidence: 99%